(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In this paper we consider finiteness conditions of union of two finite semigroups with empty intersection. We define a special binary operation on the union of two finite semigroups. We also determine the upper rank of the Brandt semigroup Â r4(B(G; n)).